Thermal analysis of helical gear transmission system considering machining and installation error. (December 2018) - Li, Wei; Zhai, Pengfei; Tian, Jingyun; Luo, Biao
Highlights: The three-dimensional temperature field of helical gear considering machining and installation error is analyzed. The average contact stress model of tooth surface considering error is set up. The friction heat flux of the helical gear is different from the spur gear, the helical gear has a spiral angle, and its friction heat flux is distributed along the helix angle. The calculation formula of convective heat transfer coefficient which considers different surfaces of gear tooth are derived. The finite element parametric model for thermal analysis are built and it realizes the parametric modeling, automatic loading and generation of temperature field by APDL program. Abstract: Gear drives are widely used in mechanical driving devices, and the heating problem caused by the error of gear has been paid much attention. The tooth surface temperature field of helical gear considering error is studied in this paper. The calculation formula of frictional heat flux and convective heat transfer coefficient which considers different surfaces of gear tooth are derived. The friction heat flux of the helical gear is different from that of the spur gear, and the calculation method is different. This is because the helical gear has a helix angle, and its friction heat flux is distributed along the helix angle. The finite element parametric model for thermal analysis are built and it realizes the automatic parametric modeling, loading and generation of temperature field by APDL program. The simulation analysis and experiment are compared to validate the accuracy of thermal analysis results. The three-dimensional temperature field of helical gear considering machining and installation error is observed. The research result reveals the larger the machining error is, the larger the temperature fluctuation is. And the tooth surface temperature of the gear increase with the increase of the machining error. When the installation error exists, the distribution of the temperature field is offset. The research of tooth surface temperature of helical gear considering error provides technical support for gear anti-scuffing calculation and optimization design. Graphical abstract: The temperature distribution of the helical gear with the comprehensive error The temperature field of the helical gear is simulated and analyzed under comprehensive errors. The larger the machining error is, the more obvious the temperature fluctuation along the direction of the tooth width. And the overall temperature of the gear increases with the increase of the machining error. When there is installation error, the overall temperature distribution of gear is offset towards the direction of installation error. And with the installation of the error increases, the offset of overall temperature field is also more obvious.Image, graphical abstract